Upaya Meningkatkan Kecepatan Menggiring Bola Dengan Menggunakan Metode Latihan Running With The Ball Dalam Permainan Sepakbola Pada Siswa Kelas XI SMA Negeri Khusus Olahraga Maluku Utara - Isnardi Ismail; Triana Nuryastuti; Syahril Arga Wabula (Peneliti.net, 2022)
Research aims to improve dribbling skills in North Maluku Special High School Sports and find out whether the running with the ball training method can increase the dribbling speed of North Maluku Sports Special High School student in soccer games. This type of research is classroom action research (action research). The population in this study was class XI student with 11 students. The method in this study used classroom action research methods, such as Pre-Tes, Ciyle I Tes and Cycle II Test. From the results of the study, it was shown that the practice of the running with the ball method was able to improve student learning outcomes for class XI SMA Negeri Special Sport North Maluku, academic Year 2022/2023. The increase in student learning outcomes can be seen from the learning outcomes achieved though the procision of tests, such as Pre-Tes, Cycle I Tes and Cycle II Test. In the learning process in the Pre-Tes with 11 students, 2 students or (18,18%) in the learning process in the first cycle the number of students who completed 6 or (54,54%) In the second cycle learning process the number of stdents who completed as many as 10 people or (90,90%).